NAZAL POLİP VE/VEYA ALERJİK RİNİTLİ HASTALARDA TH1/TH2 DENGESİ İLE 1?, 25-DİHİDROKSİVİTAMİN D3 ARASINDAKİ İLİŞKİ - ÖZKARA, ŞULE (Fırat Üniveristesi, 2011)
Bu çalışma ile izole polip, nazal polip ve/veya alerjik riniti olan hastalarda immun yanıtta rol oynayan IL-4, IL-10 ve IFN-? sitokinlerinin düzeylerini ölçerek Th1/Th2 hücre dengesini araştırmayı ve bu denge ile D vitamininin aktif metaboliti olan 1?, 25-dihidroksivitamin D3 arasındaki ilişkiyi belirlemeyi amaçladık.Çalışma 160 erişkin olgu üzerinde yapılmıştır. Çalışmada hastalar beş gruba ayrılmıştır. Sadece alerjik rinit tanısı alan hastalar grup I, alerjik rinit ve nazal polipozis tanısı alan hastalar grup II, izole polip tanısı alan hastalar grup III, alerjik riniti olmayan, nazal polipozis tanısı alan hastalar grup IV, izole polip, nazal polip ve/veya alerjik riniti olmadığı belirlenen sağlıklı gönüllü bireyler grup V'i oluşturmuştur. Bütün hastaların serum örneklerinde IFN-?, IL-4, IL-10 ve total IgE seviyeleri, plazma örneklerinde ise Vitamin D3 tayinleri yapılmıştır.Alerjik rinit grubu ve alerjik rinit+nazal polipozis grubunun IgE, IL-4, IL-10, IFN-? ve D vitamini değerleri ile kontrol grubunun IgE, IL-4, IL-10, IFN-? ve D vitamini değerleri arasında istatistiksel olarak anlamlı bir farklılık tespit edilmiştir (p<0.05).Alerjik rinit grubunda; IL-10 değerleri ile D vitamini değerleri arasında negatif yönde; alerjik rinit ve alerjik rinit + nazal polip grubunda; IgE, IL-4 değerleri ile D vitamini değerleri arasında negatif yönde; IFN-? değerleri ile D vitamini değerleri arasında pozitif yönde korelasyon saptanmıştır (p<0.05).Bu çalışmada, D vitamininin alerjik rinitli hastalarda Th1/Th2 dengesini etkilediği ve D vitamini eksikliği ile alerji arasında anlamlı bir ilişki olduğu gösterilmiştir. D vitamini eksikliği ile nazal polipozis ve izole polip arasında anlamlı bir ilişki bulunamamıştır.Anahtar Kelimeler: Nazal polipozis, İzole polip, Alerjik Rinit, D vitamini, Th1, Th2

THE RELATION BETWEEN TH1/TH2 BALANCE AND 1?, 25-DIHYDROXYVITAMIN D3 IN THE PATIENTS WITH NASAL POLYP AND/OR ALLERGIC RHINITISIn this study we aimed to investigate Th1/Th2 cell balance by measuring the levels of IL-4, IL-10 and IFN-? cytokines that play important role in immune response in patients with isolated polyp, nasal polyp and/or allergic rhinitis, and by this way it was aimed to determine the relationship between this balance and 1?, 25- dihydroxyvitamin D3, which is the active metabolite of D vitamin.The study was performed in 160 adult subjects. The patients were separated into five groups. Patients diagnosed only with allergic rhinitis formed group I, patients with allergic rhinitis and nasal polyposis constituted group II, patients with isolated polyp formed group III, patients diagnosed with nasal polyposis but no allergic rhinitis formed group IV, and healthy voluntary individuals without nasal polyp and/or allergic rhinitis were considered in group V. IFN-?, IL-4, IL-10 and total IgE levels were determined in serum samples of all patients, while vitamin D3 was determined in plasma samples.A statistically significant difference was detected between allergic rhinitis group, allergic rhinitis + nasal polyposis group and control group concerning the levels of IgE, IL-4, IL-10, IFN-? and vitamin D (p<0.05).There was a negative correlation between IL-10 and vitamin D values in allergic rhinitis group; similarly, there was a negative correlation between IgE, IL-4 and vitamin D values in allergic rhinitis and allergic rhinitis + nasal polyp groups, while a positive correlation was determined between IFN-? and vitamin D values in the same groups (p<0.05).The present study demonstrates that vitamin D is effective on Th1/Th2 balance in patients with allergic rhinitis and there is a significant relation between vitamin D deficiency and allergy. However, no significant relation was detected between vitamin D deficiency, nasal polyposis and isolated polyp.Key words: Nasal polyposis, Isolated polyp, Allergic Rhinitis, Vitamin D, Th1, Th2
The relatıon between Th1/Th2 balance and 1?, 25-dıhydroxyvıtamın D3 ın the patıents wıth nasal polyp and/or allergıc rhınıtıs
Keywords: Kulak Burun ve Boğaz